Justice for none [a novel] - Hackman, Gene 1930-2025 (St. Martins Press, 2004)
World War I veteran Boyd Calvin is wrongfully convicted of his wife's murder, and while serving his prison sentence, he meets an African-American convict who helps Boyd escape and prove his innocence.
Keywords: Weltkrieg (1914-1918); African American men -- Fiction; False testimony -- Fiction; Fugitives from justice -- Fiction; Male friendship -- Fiction; Race relations -- Fiction; Suspense fiction.; Women journalists -- Fiction; World War, 1914-1918 -- Veterans -- Fiction; Illinois -- Fiction; Historical fiction; Suspense fiction